Cooperation for reputation: Wasteful contributions as costly signals in public goods - Van Vugt, Mark; Hardy, Charlotte L. (Group processes & intergroup relations, 2010)
Why do people persistently contribute to public goods and does it matter to them if their donation makes a difference? A costly signalling perspective suggests that donors might be more concerned about their reputation than the utility of their helping act. We report data on two step-level public goods experiments. We find that in public (vs. private) conditions, contributions go up even when the public good is already provided (Experiment 1) or is unattainable (Experiment 2). Furthermore, these conspicuous donations appear to enhance the status and prestige of the donor because they signal some hidden quality. This research suggests that a public good contribution can be a self-presentation strategy and that the benefits of these contributions to society are sometimes of secondary importance.